2021
DOI: 10.4236/ojbm.2021.93067
|View full text |Cite
|
Sign up to set email alerts
|

Managing Peer-to-Peer Cooperation Using Knowledge-Based Trust and Encouraging the Willingness to Share Tacit Knowledge

Abstract: Despite leaders' investment in knowledge management practices, 76% of U.S. employees are hesitant to share tacit knowledge with co-workers. Researchers have suggested that willingness to share hinders the tacit knowledge transfer process. Employees become unwilling to share tacit knowledge with others due to cooperation and competition. The aim of this research is to understand the role of peer-to-peer cooperation on willingness to share tacit knowledge (WSTK). A total of 250 U.S. employees were sampled to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
4
0
2
Order By: Relevance
“…Scholars have argued that the in an organization, knowledge sharing can occur in leader-subordinate and among the peers horizontally (Connelly and Zweig, 2015;Razmerita et al, 2016). Hence the researchers stated that the PI and cooperation can positively affect TKS willingness (Fuller, 2021), which may further affect innovation in a particular sector. Because, the enterprise's innovative capability requires peers to work together in a collorborative culture or environment, meet expectations and attain organizational goals (Muhammed and Zaim, 2020).…”
Section: Peer Influence (Pi)mentioning
confidence: 99%
“…Scholars have argued that the in an organization, knowledge sharing can occur in leader-subordinate and among the peers horizontally (Connelly and Zweig, 2015;Razmerita et al, 2016). Hence the researchers stated that the PI and cooperation can positively affect TKS willingness (Fuller, 2021), which may further affect innovation in a particular sector. Because, the enterprise's innovative capability requires peers to work together in a collorborative culture or environment, meet expectations and attain organizational goals (Muhammed and Zaim, 2020).…”
Section: Peer Influence (Pi)mentioning
confidence: 99%
“…Se requieren acercamientos de diseño novedosos para atender la escasez de atención por medio de apalancar el pensamiento divergente y el desempeño colectivo basado en procesos de retroalimentación y en una intensa interacción social (Ioi et al, 2012;Liebowitz y Paliszkiewicz 2019;Mato de la Iglesia, 2018;McMillan 2016). Analizar los aspectos sociales inherentes a la creación y transferencia del conocimiento es fundamental para la GC, pues así se pueden implementar prácticas que promuevan compartir el conocimiento tácito y ayudar a la creación de conocimiento organizacional (Fuller, 2021;Doherty y Cormican, 2017;Watad, 2019). La TC es un paso en la GC y es un aspecto clave para gestionarlo porque, sin ese paso, la TC se vería afectada.…”
Section: Gestión Del Conocimiento Y Transferenciaunclassified
“…La TC implica un movimiento del conocimiento desde un nivel individual hasta llegar al nivel de la organización y fuera de ella (Banerjee et al, 2018). Existen diferentes aproximaciones para analizar la TC abordando el tema desde perspectivas de capacidades dinámicas, capacidades de absorción, importancia de aspectos sociales como la confianza entre compañeros y en la organización, «docilidad», colaboración etc., (Banerjee et al, 2018;Becerril Elías y Merrit, 2021;Dei y van der Walt, 2020;Fuller, 2021;Human, 2020;Ioi et al, 2012;Li et al, 2021;Londoño Patiño y Acevedo-Álvarez, 2018;McMillan, 2016;Marchiori y Franco, 2020). De acuerdo con Gupta y Govindarajan, 2000, citado en Banerjee et al (2018), las capacidades de absorción como una dimensión de las capacidades dinámicas, son un determinante significativo en la transferencia del conocimiento, debido a que.…”
Section: Introductionunclassified
“…Fuller (2021b) used Lewicki and Bunker's (1996) knowledge-based trust (KBT) theory and reported that trust predicted employees' willingness to share tacit knowledge. Fuller (2021b) did not investigate the effect of ethical leadership on employee willingness to share knowledge. Therefore, this study considered ethical leadership attributes built on integrity, assurance, and pragmatism as a trust mechanism.…”
Section: Ethical Leadership and Knowledge Hidingmentioning
confidence: 99%